2021
DOI: 10.1371/journal.pone.0254576
|View full text |Cite
|
Sign up to set email alerts
|

Leadership empowering behaviour as a predictor of employees’ psychological well-being: Evidence from a cross-sectional study among secondary school teachers in Kohat Division, Pakistan

Abstract: In this technologically developed scenario, many organizations in developing countries including Pakistan have expanded the enthusiasm for understanding and creating an encouraging administrative and managerial environment. Numerous organizations are struggling for structural changes by deserting the old-fashioned organizational management style and implementing an empowering leadership where leaders give more authority to subordinates in decision making and responsibilities with the aim to increase organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
(113 reference statements)
0
10
0
4
Order By: Relevance
“…Research has found that higher empowering leadership leads to positive employee outcomes, such as job well-being (Park et al, 2017). Adopting empowering leadership may be a way to promote teachers well-being and inspire positive employee work through enhanced job meaning, thereby contributing to their growth and development (Suleman et al, 2021). In addition, in the field of kindergarten education, empowering leaders can give them more autonomy and flexibility to respond to the challenges and difficulties of COVID-19 rather than just implementing the arrangements and instructions of their superiors (Liu et al, 2021).…”
Section: The Relationship Between Empowering Leadership and Well-bein...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that higher empowering leadership leads to positive employee outcomes, such as job well-being (Park et al, 2017). Adopting empowering leadership may be a way to promote teachers well-being and inspire positive employee work through enhanced job meaning, thereby contributing to their growth and development (Suleman et al, 2021). In addition, in the field of kindergarten education, empowering leaders can give them more autonomy and flexibility to respond to the challenges and difficulties of COVID-19 rather than just implementing the arrangements and instructions of their superiors (Liu et al, 2021).…”
Section: The Relationship Between Empowering Leadership and Well-bein...mentioning
confidence: 99%
“…For example, empowering leadership, as an important management function, this is therefore an important factor in promoting preschool teachers' well-being (Liu et al, 2021). Past research has indicated that empowering leadership is strongly associated with teacher well-being, affecting, among other things, teachers' ability to participate in decision-making and problem-solving on their own (Suleman et al, 2021). In addition, preschool teachers, as important members of kindergarten education institutions, especially during the COVID-19 pandemic, would benefit from more empowerment to increase their intrinsic motivation and positive behaviors (Siswanti and Muafi, 2020), while influencing their work through aspects such as emphasizing the meaning of their work, promoting participation in decision-making status (Bharadwaja and Tripathi, 2021), and to mitigate the negative effects of the epidemic's impact in a more flexible manner, thus having an impact on preschool teachers' well-being.…”
Section: Introductionmentioning
confidence: 99%
“…All the secondary school teachers (SSTs) of the abovementioned districts were the population of the study. 30% of the sample subjects were chosen from each district (Suleman et al, 2021). So, using a stratified random sampling technique, a total of 564 SSTs (Male n = 379; Female n = 185) were included in this study (see Table 1).…”
Section: Research Methodology Participantsmentioning
confidence: 99%
“…In educational research terminology, the research design is the overarching technique used by the researcher towards systematically and logically manage the different aspects of the study to successfully resolve the research problem. It offers framework for the systematically gathering, measuring, and interpreting data (Vaus, 2006;Suleman et al, 2021). The research design of the study offers a sufficient foundation.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these factors are limited to the individual, while others are found within the environment one operates [ 10 , 11 , 12 ]. One of the important factors that may influence psychological well-being, especially in the workplace, is leadership style [ 13 ]. Leadership is key to an organization’s performance, sustainability, and success in the market [ 14 ].…”
Section: Introductionmentioning
confidence: 99%